Production of fungal lipases using wheat bran and soybean bran and incorporation of sugarcane bagasse as a co-substrate in solid-state fermentation - Fleuri, Luciana Francisco [UNESP]; Oliveira, Mariana Cassani de [UNESP]; Campos Arcuri, Mariana de Lara [UNESP]; Capoville, Bruna Luiza [UNESP]; Pereira, Milene Stefani [UNESP]; Okino Delgado, Clarissa Hamaio [UNESP]; Novelli, Paula Kern [UNESP] (Korean Society Food Science & Technology-kosfost, 2014)
Fungal strains were screened for lipase producing activities and 10 strains were classified as good producers. Aspergillus sp., Fusarium sp., and Penicillium sp. exhibited the highest activities when fermented in wheat bran (WB) and soybean bran (SB). No fungal growth was observed using sugarcane bagasse (CB). An experimental design was applied to incorporate CB into the fermentation process for lipase production by Aspergillus sp. and Penicillium sp., and to evaluate the best moisture content for the substrate. Strains studied achieved maximum lipase activities with 25% CB combined with 75% WB or SB at 40% moisture content. The highest lipase activities were observed for WB and SB, and for SB combined with CB using Aspergillus sp. Fermentation of 96 h was the optimum period for enzyme production.
Keywords: lipase; fungi; solid-state fermentation; Aspergillus sp.; Penicillium sp.; enzyme production